PENGARUH KOMITE AUDIT, RASIO KEUANGAN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK - Fanny Anggraeni; Patricia Michelle (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this study is to obtain empirical evidence regarding the effect of independent variables on tax avoidance. The independent variables used are audit committee, leverage, return on assets, company size, sales growth and corporate social responsibility. The statistical testing techniques used are multiple regression and hypothesis testing. This study uses secondary data. The secondary data of research was obtained by sampling. The sampling method used is purposive sampling. There are 175 data manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020 that meet the criteria. The results of the study indicate that several independent variables have an effect on the dependent variable and several independent variable have no effect on the dependent variable. The sales growth variables have a negative effect on tax avoidance. While the variables of audit committee, leverage, return on assets, company size and corporate social responsibility have no effect on tax avoidance.